Rape incidence among children and teenagers in rural and urban communities in Nigeria - Sulaiman, Afolasade Airat; Tahir, Babatunde Muyideen; Olupooye, Olabusoye; Wusu, Onipede; Olateju, Adijat Olubukola; Aliu, Ibrahim Rotimi; Raji, Shakiru Olarotimi; Moa-Liberty, Alausa Waheed; Omobitan, Olufunsho Abayomi (INSPIRA: Indonesian Journal of Psychological Research, 2024)
This study investigated the incidence of rape among children and teenagers in rural and urban communities in Nigeria. The study employed a cross-sectional survey design to describe the experiences of children and teenagers purposively selected from the six geopolitical regions of Nigeria. 445 participants between the ages of 9 and 19. Results revealed 10.7% rape incidence and 32.8% sexual experience two years before the study for respondents. Age, ethnicity, and community variations were found for rape incidence with 11.8% higher among teenagers aged 13 and above, 7.4% higher in urban communities and a high percentage of 27.2% among the Hausas. Advocating for strict legislative reforms to address the stringent procedures in establishing rape incidents in Nigerian law, comprehensive sexuality education programs in schools to promote awareness and healthy relationships, and preventive counselling interventions were recommended. The study provided an understanding of rape incidence among children and teenagers in Nigeria.